Oppositional defiant disorder and conduct disorder in DSM IV - Grzywa-Bilkiewicz, Agnieszka; Śpila, Bożena; Grzywa, Anna (Current Problems of Psychiatry, 2011)
The study discusses the qualification criteria of oppositional defiant disorder and conduct disorders according to DSM IV TR. These disorders occur in the children and adolescents population. The oppositional defiant disorder is manifested as inadequate for a particular age behavior, tenacious, unpleasant, argumentative, rebellious, purposefully irritating, sensitive, revengeful tending to blame others for own offences and negligent conduct. The oppositional defiant disorder usually precedes conduct disorders development; and the conduct behavior encompasses the defiant attitude; however, only up to 25% of children with oppositional defiant disorder in the pre-school age develop the conduct disorders later on. Conduct disorders include various forms of destructive behaviors. Genetics, epidemiology of the prevalence of these disorders by gender, differential diagnosis with other disorders of the developmental age, including ADHD, have been researched and discussed. Dynamics and clinical picture of the disorders along with the development of the child, have been investigated. It was discovered that the patterns of disruptive behaviors come up as a result of combination of neurobiological risk factors, attachment disorders, inadequate parental practices as well as pathological family environment.